2020
DOI: 10.1038/s41467-020-14461-3
|View full text |Cite
|
Sign up to set email alerts
|

Early life experiences selectively mature learning and memory abilities

Abstract: The mechanisms underlying the maturation of learning and memory abilities are poorly understood. Here we show that episodic learning produces unique biological changes in the hippocampus of infant rats and mice compared to juveniles and adults. These changes include persistent neuronal activation, BDNF-dependent increase in the excitatory synapse markers synaptophysin and PSD-95, and significant maturation of AMPA receptor synaptic responses. Inhibition of PSD-95 induction following learning impairs both AMPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 64 publications
6
42
0
Order By: Relevance
“…These mechanisms overlapped with those that had previously been discovered to be engaged during sensory critical periods, and they included a BDNF-and metabotropic glutamate receptor-5-dependent switch in the expression of the NMDAR subunits, from 2B to 2A (Travaglia et al, 2016). Learning-induced changes also included persistent neuronal activation measured by induction of immediate early genes, BDNF-dependent increases in the excitatory synapse markers synaptophysin and PSD-95, and significant maturation of AMPAR synaptic responses (Bessières et al, 2020). These data led to the conclusions that (1) the hippocampus, like sensory systems, undergoes a developmental critical period to become functionally competent; and (2) on learning a specific stimulus/context association, the infant hippocampus has heightened neuronal activation that follows a distinct kinetic from the adult hippocampus, and can last for up to 48 h after learning.…”
Section: Experience-dependent Maturation Of Hippocampusdependent Memory Functionsmentioning
confidence: 75%
See 1 more Smart Citation
“…These mechanisms overlapped with those that had previously been discovered to be engaged during sensory critical periods, and they included a BDNF-and metabotropic glutamate receptor-5-dependent switch in the expression of the NMDAR subunits, from 2B to 2A (Travaglia et al, 2016). Learning-induced changes also included persistent neuronal activation measured by induction of immediate early genes, BDNF-dependent increases in the excitatory synapse markers synaptophysin and PSD-95, and significant maturation of AMPAR synaptic responses (Bessières et al, 2020). These data led to the conclusions that (1) the hippocampus, like sensory systems, undergoes a developmental critical period to become functionally competent; and (2) on learning a specific stimulus/context association, the infant hippocampus has heightened neuronal activation that follows a distinct kinetic from the adult hippocampus, and can last for up to 48 h after learning.…”
Section: Experience-dependent Maturation Of Hippocampusdependent Memory Functionsmentioning
confidence: 75%
“…While there is reason to believe that complex forms of episodic memory are not formed early during life, there is also very good reason to suspect that some hippocampus-dependent learning and memory mechanisms are indeed available to infants. In rodents, hippocampal neurons are already able to tune their activity to experience-dependent variables during infancy (Langston et al, 2010;Wills et al, 2010), and can create long-lasting biological changes supporting synapse maturation where memories of early-life events are encoded (Travaglia et al, 2016;Bessières et al, 2020). In humans, it has been more difficult to assess this issue.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic treatments that promote synaptic plasticity may have potential benefit for patients with early or prodromal AD. Synaptophysin and PSD-95 are two synapse-associated proteins that are important for the formation of long-lasting, latent memories (Bessieres et al, 2020). Our study suggested that the levels of these two proteins were significantly decreased in Aβ1-42-treated mice, but PDE4D deficiency in the prefrontal cortex increased the expression of synaptophysin and PSD-95, indicating the role of PDE4D inhibition in amelioration of synaptic plasticity and neuronal atrophy in the progression of AD.…”
Section: Discussionmentioning
confidence: 59%
“…S2 A and B). Moreover, we found evidence for the functional integration of neurons generated after indole supplementation through an assessment of synapse expression based on the presence of presynaptic synaptophysin (SYP) and postsynaptic density 95 (PSD-95) in the hippocampus (64). Indole-supplemented mice displayed increased PSD-95 and SYP mRNA in the hippocampus compared with controls (Fig.…”
Section: Systems Biologymentioning
confidence: 84%